Genealogia e literatura menor em Herculine Barbin (1838 –1868) - Mação, Izabel Rizzi (2022)
Adèlaïde Herculine Barbin was a French teacher diagnosed as a male hermaphrodite at the age of 21. After having her civil status rectified, she was renamed Abel Barbin. In 1868, already living as a man, Herculine committed suicide. Beside her body, the manuscript My Memories was found, in which she narrated the misadventures and joys of her brief existence. Rediscovered by Michel Foucault in the late 1970s, the document was published, together with other sources, under the title Herculine Barbin dite Alexina B. The analysis of this work demonstrates that a question was insistently addressed to Herculine: what was her true sex? She, however, disarticulated and returned the question to the sexuality device, asking it as follows: do we really need a true sex? Following this small question raised by Herculine, we are dedicated to elucidating the obstinacy of medical knowledge, especially those developed at the end of the 19th century in Europe, for revealing the true sex of individuals considered uncertain. We also pay attention to the potentialities expressed by Herculine to escape the dictates of univocal sexual distinction and the power devices that sought to tame her difference. To carry out this investigation, we used several methodological tools, with emphasis on genealogy – as thought by Friedrich Wilhelm Nietzsche, Gilles Deleuze and Michel Foucault – and on minor literature, according to Deleuze and Félix Guattari's proposal.